2018
DOI: 10.1155/2018/9795654
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced Coffee-Ring Effect via Substrate Roughness in Evaporation of Colloidal Droplets

Abstract: The analysis of dried drop patterns has various applications in research fields like archeology, medical practice, printing, and so on. In this paper, we studied the evaporation and pattern formation of polytetrafluoroethylene (PTFE) colloid droplets on smooth substrate and rough substrates with different roughness. We found that the evaporation of droplets shows remarkable coffee-ring effect on smooth substrate and that the cross-section of the ring is wedge-shaped with its thickness decreasing from the edge … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
21
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(24 citation statements)
references
References 20 publications
3
21
0
Order By: Relevance
“…The coffee ring effect is less apparent, possibly due to the smoother surface of mirror aluminium. This concurs with research by Zhang, Chen [ 23 ] who found that the roughness of the surface strengthened the coffee ring effect because the rough structure inhibited the backflow of the capillary flow, preventing the particles’ move to the centre. Still, the majority of misclassified pixels of E. coli at 10 OD are found at the outside layer, which is consistent with the prediction maps of stainless steel.…”
Section: Resultssupporting
confidence: 91%
“…The coffee ring effect is less apparent, possibly due to the smoother surface of mirror aluminium. This concurs with research by Zhang, Chen [ 23 ] who found that the roughness of the surface strengthened the coffee ring effect because the rough structure inhibited the backflow of the capillary flow, preventing the particles’ move to the centre. Still, the majority of misclassified pixels of E. coli at 10 OD are found at the outside layer, which is consistent with the prediction maps of stainless steel.…”
Section: Resultssupporting
confidence: 91%
“…When the droplet evaporates in a confined geometry, evaporating vapors are stagnated near the droplet interface and it eventually changes evaporation dynamics due to varying concentration differences, near and away from the interface [ 91 , 92 , 93 , 94 , 95 , 96 , 142 ]. In addition, substrate properties such as roughness influence the ring formation with cracks appearing at the periphery of droplets [ 99 ]. A few studies have compared the deposit patterns on the smooth and rough surfaces and analyzed the film morphology obtained after evaporation, considering the substrate roughness and other effects [ 100 ].…”
Section: Effect Of Geometrymentioning
confidence: 99%
“…This method has been widely used due to simple and effective control of the deposition but remains limited in biochemical applications because it causes contamination. Other strategies without modifying the composition of the droplet have been introduced, where drying conditions [ 73 , 74 , 75 , 76 , 77 , 78 , 79 , 80 , 81 , 82 ] or geometry [ 83 , 84 , 85 , 86 , 87 , 88 , 89 , 90 , 91 , 92 , 93 , 94 , 95 , 96 , 97 , 98 , 99 , 100 ] can be changed. Recent works have reported the effect of external sources including external vapor [ 101 , 102 , 103 , 104 , 105 , 106 ], magnetic field [ 107 , 108 ], and surface acoustic wave (SAW) [ 52 , 109 ] on the deposit patterns.…”
Section: Introductionmentioning
confidence: 99%
“…Droplet evaporation has attracted increasing attention in recent decades, with its wide application in the industrial field. Commonly seen applications of droplet evaporation are Inkjet printing [1,2], spray cooling [3], material processing [4], coffee-ring effect [5][6][7][8] and particle synthesis [9,10]. In recent years, more medical applications have been developed for droplet evaporation, like DNA/RNA arrangement [11,12] and medical diagnosis [13,14].…”
Section: Introductionmentioning
confidence: 99%